The screening for marine fungal strains with high potential in alkaloids production by in situ colony assay and LC-MS/MS based secondary metabolic profiling - Lu, Tiantian; Liu, Yayue; Zhou, Longjian; Liao, Qingnan; Nie, Yingying; Wang, Xingyuan; Lei, Xiaoling; Hong, Pengzhi; Feng, Yan; Hu, Xueqiong; Zhang, Yi (Frontiers in Microbiology, 2023)
Alkaloids are the second primary class of secondary metabolites from marine organisms, most of which have antioxidant, antitumor, antibacterial, anti-inflammatory, and other activities. In this study, we utilized in situ colony assay combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) to identify the strain with high potential in alkaloids production. Eighteen marine fungi were preliminarily screened for alkaloids production in situ using Dragendorff reagent as dye, and nine of them turned orange, which indicated abundant alkaloids. By thin-layer chromatography (TLC), LC-MS/MS, and multiple approaches assisted Feature-Based Molecular Networking (FBMN) analysis of fermentation extracts, a strain ACD-5 (Penicillium mallochii with GenBank accession number OM368350) from sea cucumber gut was selected for its diverse alkaloid profiles especially azaphilones. In bioassays, the crude extracts of ACD-5 in Czapek–dox broth and brown rice medium showed moderate antioxidant, acetylcholinesterase inhibitory, anti-neuroinflammatory, and anti-Aβ aggregation activities. Three chlorinated azaphilone alkaloids, compounds 1–3 (sclerotioramine, isochromophilone VI, and isochromophilone IX, respectively), were isolated from the fermentation products of ACD-5 in brown rice medium guided by bioactivities and mass spectrometry analysis. Compound 1 had shown remarkable anti-neuroinflammatory activity in liposaccharide induced BV-2 cells. In summary, in situ colony screening together with LC-MS/MS, multi-approach assisted FBMN can act as an efficient screening method for strains with potential in alkaloids production.